Gestão de segurança de contratados em serviços de caldeiraria - Estudo de caso em uma indústria de produção, envasamento e expedição de óleos lubrificantes - Silva, Marcio Valerio Santos da (2003)
Focused in concentrating on their own critical activities, organizations are outsourcing their support activities. lii petroleuni industries this practice is used on activities that need people with special qualification. The OSHAS 18001 standard requires for a suitable control of outsourced activities. This shows that we must integrate many isolated programs and actions in order to have an effort synergy. The objective of this research is to identify opportunities for establishing a safety management system for the hired employees in a production, envasing and shipping lubricant oil industry. The introduction of outsourced employees within the limits of manufacturing labor claims a safety management system for this set of employees. The development of this paper was achieved tbrough a bibliographic search, that was based on national and intemational documents that deal with contractors safety management. Thus, important references are presented so that great organization safety managers can acquire sufficient knowledge in procedures and practices related to the implementation of service contracts. Among the obtained references, the author chose to use a hired companies health and safety management program that is based on continuous improvement, known as PDCA (Plan, Do, Check, Act). This work presents the opportunities and difficulties in evaluating outcome in the implementation of this program in a áontract for heavy mechanics maintenance in the analysed industry. The case study allowed us to fmd that a theoretical model must be tested in practice for a reflection about its feasibility. lii tbis paper, this fact was considered. With tbis, a safety management system model for contractors is presented and takes into account a customization of a model taken from literature, according tu the company and the contracted employees profiles. It is essential that the contracted companies assume their part on the responsibiity of risk management of their activities. The contracting companies should establish a model of risk management that doesn t consist only on the attendance of the applicable law by the contractors. They must establish safety planning requirements. The research allowed us to see the services contracting configuration influences iii the approach of the management system. The best situation is the one where the contractor itself controis the services performance. Another important confirmation is that a management system must be concentrated in the identification of activities risks.